Developing Online Competition Law Educations Tools for SMEs - Schaper, Michael; Cejnar, L. (ISEAS Publishiing, 2016)
This book seeks to rectify the relative neglect in research and policy discussions on the role of the SME sector in competition policy and law. Drawing on contributions from a wide range of competition regulators, lawyers, academics, consultants and advisers to the SME sector, it addresses such important issues as: perceptions and views of small businesses about competition law; regulator engagement and education of the SME sector; the link between competition law and economic growth; franchising, SMEs and competition law; issues in enforcing competition law against SMEs; the role of Chinese family firms; trade, professional and industry associations; country case studies from Vietnam, Singapore, Indonesia, Malaysia, China, South Korea, Hong Kong SAR, Japan and the Pacific Islands.